Pengembangan Instrumen Penilaian Unjuk Kerja pada Materi Membaca Puisi di SMA - Ratri, Saras Madia Ratri (J-LELC: Journal of Language Education, Linguistics, and Culture, 2022)
What are the stages of development and the level of validity, practicality, and effectiveness of developing an instrument for assessing the performance of poetry reading materials at SMAN 1 Pekanbaru. The aim is to develop and produce an instrument for assessing performance on poetry reading material at SMAN 1 Pekanbaru that meets the criteria of being valid, practical, and effective. This research is research and development. Researchers will use 3D models. There are 3 stages, namely Define, Design, and Develop. The research was conducted at SMA N 1 Pekanbaru class X IPA 1 and 2 totaling 35 students. Based on the analysis carried out on the validation of the instrument, it was developed to achieve an average score level of the final score of all validators of 91% in the very valid category. The results of the educator practicality questionnaire analysis show that the average score of the final grades of all practitioners. The performance assessment instrument is 97% in the very practical category. From the observation of student learning activities carried out by Indonesian language subject educators based on data analysis, it can be categorized as very effective with a percentage value of 82.85%. From the overall results of validation, practicality, and effectiveness, it can be concluded that the Poetry Reading Material Performance Assessment Instrument produced is valid, practical, and effective. Thus the Poetry Reading Material Performance Assessment Instrument that was developed can be used by educators and students in learning to read poetry for high school class X.